Open Government: Key Issues in Latvia - Syed Agung Afandi; Rizki Erdayani; Muslim Afandi (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2024)
This study aims to find out how the management of Sedana Mekar BUMDes applies the principles of village autonomy in Mekarsari village, East Lore sub-district, Poso district. This research was conducted in the village of Mekarsari, East Lore sub-district, Poso district with the theory of village autonomy put forward by Sutoro Eko (2014), which is Impunity and Initiative. The research method uses qualitative with descriptive research type. The technique of determining informants used a purposive sampling technique with 6 informants. Data collection techniques were carried out by means of observation, interviews and documentation. The results of this study concluded that the implementation of the principles of village autonomy in the management of BUMDes Sedana Mekar in Mekarsari village was considered not optimal. This is based on aspects of Sutoro Eko's theory used in this study, namely the principle of impunity and initiatives in the management of BUMDes Sedana Mekar. Inadequate planning often occurs in BUMDes management so that the initiatives implemented are not optimal. And it is also found that there are irregularities in the principle of impunity, namely the appointment of BUMDes administrators from village officials which causes the village oversight function of BUMDes to become village oversight of itself.